Morphological data and ecological niche modelling support the inclusion of Phaseolus rubidus in Macroptilium: Implications for Papilionoid Lineages in the Cerrado and Paraná Forests - Ribeiro, Carolina Lima; Da Silva Santos, Felipe; Snak, Cristiane; Paganucci De Queiroz, Luciano (Phytotaxa, 2025)
The identity of Phaseolus rubidus has been controversial due to its similarity to Macroptilium erythroloma and M. monophyllum. Based on niche modelling and a detailed morphological analysis, we propose that Phaseolus rubidus should be reinstated as a distinct species and classified within Macroptilium. Macroptilium rubidum can be distinguished from other species by the combination of erect habit, generally reddish velutinous indumentum, leaves with one to three leaflets, leaflets ovate, never lobed, and peduncular bracts at the base of the inflorescence and floral bracts that are equal to or smaller than the calyx. It occurs in the northeast of Argentina, southern Brazil, and Paraguay, within the Paraná Forest province, having an ecological niche restricted to the open fields of temperate and humid environments in this biogeographical province.